General Layout Optimization for Fusion Power Plant - Xinkai LI; Kui XIANG; Hua LI; Guangtao ZHU (南方能源建设, 2022)
[Introduction] The general layout of the plant has great significance for the conceptual design process of the China Fusion Engineering Test Reactor (CFETR). Herein, preliminary exploration of the fusion power plant general layout has been conducted by comparing various energy storage system selection and planning energy storage area layout. [Method] This research analyzed the energy flow characters of the fusion power plant, energy storage technology route and the characteristics of heat storage materials. Techno-economic comparisons have also been given among four plans of various combination of heat storage methods and their layouts. [Result] We find that the molten salt storage solution has outstanding economic strengths, but its high temperature corrosion has a greater impact on the safety operation and maintenance of nuclear power plants, while the heat transfer oil solution is just the opposite. Therefore, the results show that triangular arrangement or tandem arrangement of energy storage areas with nuclear islands and conventional islands can well meet the thermal system of the whole plant and the thermal operation flow direction of the energy storage system, which is in line with the general layout requirements. [Conclusion] In conclusion, the energy storage technology route and the arrangement of the storage area are key factors affecting the layout of fusion power plants. The layout presented in this paper are all well adapted to the thermal operation of the newly added energy storage system that may be applied in the fusion power plant general layout.